Analysis of Factors Associated with The Quality of Life of Clients with Schizophrenia in Outpatient Ward in Nasional Mental Health Hospital - Bunga Permata Wenny; Rr. Achir Yani; Dewi Eka Putri (Faculty of Nursing, Universitas Andalas, 2018)
Background: The life quality of schizophrenic clients is influenced by individual factors (age, sex, educational status, employment status, marital status), disease factors (ever treated, history of substance abuse, suicide history, history of violent behavior) and family factors (living with offenders, family support and family burden). Purpose: To analyze factors related to quality of life of skizofrenia clients in outpatient installation in National Mental Health Hospital. Method: The type of this research is descriptive correlative with cross sectional approach with the number of respondents 152 people. The sampling technique used is purposive sampling. Result: The results showed that there was a significant relationship between employment status, marital status, previous care, living with care giver, family support, and family burden on the life quality of schizophrenic patients (p <0.05). Conclusion: There was no significant association between age, sex, educational status, history of substance abuse, suicide history, history of violent behavior with life quality. The most dominant factor in this study was to stay with care giver ((coeffecients B = -5.577).